Economic growth in India revisited: an application of cointegration and error correction mechanism - Haldar, Sushil Kumar (2009)
This article tries to examine the relevance of the three distinct types of the growth models, namely, physical capital accumulation - led growth, export-led growth and Lucas-type human capital accumulation-led growth in India taking a long-time series data from 1950-51 to 2003-04. Employing the Johansen's cointegration and error correction model, we find that the human capital investment plays a crucial role both in the long run as well as in the short rn. The export-led growth hypothesis a partially valid whereas the physical capital investment-led growth appears to be insignificant in our findings. - Reproduced.
Keywords: Economic growth -India; Economic growth